Luxação extrusiva em primeiros molares de ratos: desenvolvimento de modelo experimental - CANTANHEDE, Luana Martins (2014)
Experimental studies in rats may be useful for understanding the repair process of mature teeth that suffered extrusive luxation. The purpose of this study was to establish a replicable experimental method with standardized direction and intensity of the force, capable of producing clinical and histological changes consistent with extrusive luxation in murine. Ten Wistar rats ( Rattus norvegicus albinos ) , adult males ( 20 teeth ) were divided into control group ( 4 teeth ) and experimental group ( N = 16 teeth 4 teeth in each subgroup). The control group were not subjected to trauma . Each experimental group was submitted to a trauma extrusive luxation with different intensity (group 1: 700 cN , group 2: 1000 cN , group 3: 1300 cN and group 4: 1600 cN ) standardized through tensiometer. It was realized a descriptive microscopic analysis of the maxillary first molar and also histometric analysis of the bifurcation. The forces of 700 and 1000 cN presented clinical and histological features of subluxation while the strength of 1300cN presented clinical and histological features compatible with extrusive luxation. The strength of 1600 cN showed no replication for this methodology. In histometric analysis, the groups showed the following averages: control group to 138.38 nm (± 23.84) , group 1 to 144.65 nm (± 22.46) group 2 to 186.77 (± 20.09), group 3 to 238.55 nm (± 25.27 nm) and group 4 to 227.94 nm (± 46.19). The strength 1300 cN was considered ideal to produce clinical and histological features of dentoalveolar trauma extrusive luxation type.